L’avvenire di Mnemosyne L’eredità di Warburg come compito per le digital humanities - Capasso, Michele (Mechane, 2024)
In many ways Mnemosyne, the Bilderatlas composed by Warburg opened up hermeneutical and critical possibilities yet largely to be explored. Through a revolutionary method, montage, and a specific technical language, photography – which allowed him to isolate gestures and details of selected artworks and materials – the critic was able to collect a “moving image” of the Modern through the survival of the Ancient. Today, on the one hand, scholars try to “operationalize” the search for types and Pathosformeln through specific algorithms; on the other hand, they experiment with and configure virtual explorations of the Warburghian archive online. Moving from Warburg’s work, this essay seeks to problematize methodological and hermeneutical issues in light of the development of the latest technologies and the possible implications for humanities and digital studies.